Enhanced output power of near-ultraviolet LEDs with AlGaN/GaN distributed Bragg reflectors on 6H–SiC by metal-organic chemical vapor deposition. (September 2015) - Tao, Pengcheng; Liang, Hongwei; Xia, Xiaochuan; Liu, Yang; Jiang, Jianhua; Huang, Huishi; Feng, Qiuju; Shen, Rensheng; Luo, Yingmin; Du, Guotong
Highlights: Crack-free UV-LED with 30 pairs AlGaN/GaN DBRs grown on 6H–SiC substrate by MOCVD. A thin SiN x interlayer was introduced to reduce the threading dislocation density. The light output power for UV-LED with DBRs was improve about 56% at 350 mA. The DBRs is not only improved efficiency of UV-LEDs, but also can be applied to RCLEDs and VCSELs. Abstract: Near-ultraviolet (UV) InGaN/AlGaN multiple quantum well (MQW) LEDs with 30 pairs AlGaN/GaN distributed Bragg reflectors (DBRs) were grown on 6H–SiC substrate by metal-organic chemical vapor deposition. A thin SiN x interlayer was introduced between the DBRs and n-GaN layer of the LED to reduce the threading dislocation density and result in enhancement the internal quantum efficiency ( ηint ) of the InGaN/AlGaN LED. The result indicates that the light output power for the LED with DBRs and SiN x interlayer was approximately 56% higher (at 350 mA) than the LED without DBRs and SiN x interlayer on 6H–SiC substrate, and this significant improvement in performance is attributed not only to the light extraction enhancement via the DBRs but also due to improve epilayer crystalline quality.